EFFECT OF ETHANOL EXTRACT OF KATUK LEAVES (Sauropus androgynus) ON MALONDIALDEHYDE LEVELS AS AN ANTIOXIDANT - Hillda Herawati; Nabila Shafira Oktaviana; Iis Inayati Rakhmat (Journal of Health and Dental Sciences, 2026)
The tooth movement that occurs when mechanical forces are applied to an orthodontic appliance can cause irritation and inflammation. This inflammation can contribute to increased oxidative stress in the oral cavity. The formation of oxidative stress can turn into a chain reaction that can continue to form new free radicals. Katuk leaves (Sauropus androgynus L. Merr) have antioxidant content that can slow down the process of free radicals. The purpose of this study was to determine the effect of the ethanol extract of katuk leaves as an antioxidant on reducing blood plasma MDA levels. The research method is a laboratory experiment using four treatment groups: blood plasma as a negative control, plasma oxidized with CuCl2 as a positive control, blood plasma given CuCl2, and ethanol extract of katuk leaves and plasma given CuCl2, and vitamin C as an antioxidant control. MDA levels were examined using the thiobarbituric acid reactive substance (TBARs) method. The data were analyzed by Anova and Tukey (p<0.05). The results showed that there was an effect of the ethanol extract of katuk leaves on malondialdehyde levels (p = 0.035) with MDA values of CuCl2 plasma (0.005 mg/dL), plasma with katuk (0.003 mg/dL), and plasma with vitamin C (0.021 mg/dL). It can be concluded that the use of ethanol extract from katuk leaves has antioxidant potential to decrease MDA levels in blood plasma. DOI : 10.54052/jhds.v5n3.p311-320